Treatment modalities favoring outcome in well-differentiated neuroendocrine tumors G3 - Hinterleitner, Martina; Pfeiffer, Ruben; Trautwein, Nils F.; Sipos, Bence; Singer, Stephan; Nadalin, Silvio; Königsrainer, Alfred; Lauer, Ulrich M.; la Fougère, Christian; Zender, Lars; Hinterleitner, Clemens (Frontiers in Endocrinology, 2024)
Neuroendocrine neoplasms (NEN) are a rare and heterogenous group of tumors arising from neuroendocrine cells in multiple organs. Neuroendocrine tumors (NET) G3 encompass a small subgroup accounting for less than 10% of all neuroendocrine neoplasms. In contrast to NET G1 and G2 as well as neuroendocrine carcinomas (NEC), in NET G3 data on treatment and patient outcomes are still limited. Especially in a metastasized tumor stage the role of surgery, peptide receptor radionucleotide therapy (PRRT) and systemic chemotherapy is not clearly defined. In this real-live cohort we consecutively analyzed clinical outcome in NET G3 patients receiving different diagnostic and treatment. We found that even metastasized NET G3 patients undergoing surgery, or receiving radiation, somatostatin analogues (SSA), and PRRT showed a clear survival benefit. Interestingly, all treatment regimen were superior to classical chemotherapeutic agents. In addition, somatostatin receptor (SSTR) PET-CT, FDG PET-CT and repetitive biopsies were shown to be useful diagnostic and prognostic tools in NET G3.Our study demonstrates that patients with highly proliferative NET G3 might benefit from less aggressive treatment modalities commonly used in low proliferative NEN.